Activation of p38MAPK contributes to expanded polyglutamine-induced cytotoxicity. - Maria Tsirigotis; R Mitchell Baldwin; Matthew Y Tang; Ian A J Lorimer; Douglas A Gray (PLoS ONE, 2008)
The signaling pathways that may modulate the pathogenesis of diseases induced by expanded polyglutamine proteins are not well understood.Herein we demonstrate that expanded polyglutamine protein cytotoxicity is mediated primarily through activation of p38MAPK and that the atypical PKC iota (PKCiota) enzyme antagonizes polyglutamine-induced cell death through induction of the ERK signaling pathway. We show that pharmacological blockade of p38MAPK rescues cells from polyglutamine-induced cell death whereas inhibition of ERK recapitulates the sensitivity observed in cells depleted of PKCiota by RNA interference. We provide evidence that two unrelated proteins with expanded polyglutamine repeats induce p38MAPK in cultured cells, and demonstrate induction of p38MAPK in an in vivo model of neurodegeneration (spinocerebellar ataxia 1, or SCA-1).Taken together, our data implicate activated p38MAPK in disease progression and suggest that its inhibition may represent a rational strategy for therapeutic intervention in the polyglutamine disorders.